A Near Miss: Case Report and Literature Review - Fahad, Alsufayan; Omar, Mohamed Adam (American Journal of Perinatology Reports, 2012)
We report a 28-week gestation premature infant with rare complication of endotracheal intubation. A piece from the plastic sheath of the stylet was retrieved inside the endotracheal tube after extubation.
Keywords: endotracheal; intubation; stylet